Penerapan Enterprise Resource Planning (ERP) Menggunakan Odoo 14 (Studi Kasus: Usaha Garmen Pada Club Ink Bali - Mahendra yana, Anak Agung Gde; Arya Sasmita, Gusti Made; Hary Susila, Anak Agung Ngurah (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2022)
Abstract Enterprise Resource Planning (ERP) is an information system that is intended for some companies such as Club Ink Bali. Club Ink Bali is a Micro, Small and Medium Enterprise or UMKM which is engaged in the manufacturing of apparel, producing a produc t that is quite productive to make Club Ink Bali often experiences problems such as product ordering systems, and other transaction recordings that do not yet use technology, resulting in a long time to place an order, loss of material information data, and transactions. Therefore, the owner feels the need for an integrated technology system, therefore the researcher feels the right solution to deal with the problems at hand is to use Odoo software to help carry out business processes in the company by using several modules such as the Sales Module, Purchase Module, Point of Sales Module, Inventory Module, Manufacturing Module, Invoice Module, and Website Module.